Numerical research on the influence of ventilation velocity on fire smoke distribution in bifurcated roadway - Cui DING (Meikuang Anquan)
In order to investigate the influence of ventilation velocity on fire smoke distribution in bifurcated roadway, the computational fluid dynamics (CFD) numerical method was adopted to simulate the fires located in upstream of main-roadway. The influence of ventilation velocity on the length of smoke backflow and the temperature distribution and CO mass concentration distribution in main-roadway and sub-roadway were analyzed. The results showed that the length of smoke backflow decreased linearly as the increasing of ventilation velocity. The average temperature at the height of breathing zone in sub-roadway was little higher than that in main-roadway downstream under different ventilation velocity condition, and the biggest temperature difference is 8 ℃. The relationship between ventilation velocity and the average temperature at the height of breathing zone in main-roadway downstream and in sub-roadway fitted in power function trend. The CO mass concentration difference between main-roadway downstream and sub-roadway decreased gradually as the increasing of ventilation velocity, and the smallest mass concentration difference was 9.25 mg/m3. The relationship between ventilation velocity and the CO average mass concentration at the height of breathing zone in main-roadway downstream and in sub-roadway fitted in power function trend. When the ventilation velocity is 1-3 m/s, the workers in the sub-roadway are less susceptible to fire smoke and toxic gases, and when the ventilation velocity is 1.5-3 m/s, the workers in the main-roadway downstream are less susceptible to fire smoke and toxic gases